Modern weapons and military equipment for issue 4-2015 - Tišma, Mladen R. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Brotherhood in action – joint exercise of the Serbian Air Force and Russian Aerospace Forces „BARS-2015“